NCDs, gender, intersectionality and the World Health Organization. (30th September 2020) - Somerville, C
Abstract: Claire Somerville, PhD (Gender Centre, Graduate Institute of International and Development Studies, Geneva) will present research that investigates how gender and intersectionality analysis of NCDs is integrated into different levels of health policy and programming and within country level health systems and services by the World Health Organization (WHO). The research is the first of its kind and is based on a WHO document analysis and key informant interviews with key representatives working on issues of gender and NCDs within WHO. The findings of Somerville's investigation reveal how gender and its intersections is understood and mainstreamed at all three organizational levels of the WHO (headquarters (HQ), regions, and country level offices) and what the key impediments are not only in terms of mainstreaming a more relational and intersectional understanding of gender in general, but specifically in relation to NCDs.